Field evidence for litter and self‐DNA inhibitory effects on Alnus glutinosa roots. Issue 2 (10th August 2022) - Bonanomi, Giuliano; Zotti, Maurizio; Idbella, Mohamed; Termolino, Pasquale; De Micco, Veronica; Mazzoleni, Stefano
Summary: Litter decomposition releases nutrients beneficial to plants but also induces phytotoxicity. Phytotoxicity can result from either labile allelopathic compounds or species specific and caused by conspecific DNA. Aquatic plants in flowing water generally do not suffer phytotoxicity because litter is regularly removed. In stagnant water or in litter packs an impact on root functionality can occur. So far, studies on water plant roots have been carried out in laboratory and never in field conditions. The effect of conspecific vs heterospecific litter and purified DNA were assessed on aquatic roots of the riparian woody species Alnus glutinosa L. using a novel method, using closed and open plastic tubes fixed to single roots in the field with closed tubes analogous to stagnant water. Four fresh and four decomposed litter types were used and analysed on extractable C, cellulose, lignin, N content and using 13 C‐CPMAS NMR spectroscopy. Inhibitory effects were observed with fresh litter in closed systems, with a positive correlation with extractable C and negative with lignin and lignin : N ratio. Alnus self‐DNA, but not heterologous one, caused acute toxic effects in the closed system. Our results demonstrate the first field‐based evidence for self‐DNA inhibition as causal factor of negative feedback between plants and substrate.